Protective anti-idiotype antibodies in the primate model of pyelonephritis. - Kaack, M B (1993)
The adherence of P-fimbriated Escherichia coli to a receptor containing alpha-D-Gal-(1-4)-beta-D-Gal (Gal-Gal) on urothelial cells is an important pathogenic mechanism in the development of pyelonephritis. Antibodies (Ab1) that had been produced by immunization with Gal-Gal conjugated with bovine serum albumin were specifically purified and used to stimulate the production of anti-idiotypic antibodies (Ab2) in cynomolgus monkeys (Macaca fascicularis). While sera from all of the Ab2-producing monkeys contained antibodies reactive with Ab1 and P-fimbriae, not all of the sera inhibited P-fimbrial binding to the Gal-Gal receptor. On the basis of the inhibition of binding, Ab2-producing monkeys were divided into two groups, termed reactive and nonreactive. The reactive and nonreactive Ab2-producing monkeys, together with a group of control monkeys, were challenged with a renal inoculation with P-fimbriated Escherichia coli. Hematologic, immunologic, microbiologic, and pathologic data were compared among the three groups. The reactive monkeys, whose Ab2 in serum inhibited binding between P-fimbriae and the Gal-Gal receptor, were protected against renal damage compared with the control group. The nonreactive group shared some parameters with the reactive group but overall developed renal damage comparable to that of the controls.